EVALUASI PELAKSANAAN ANBK DI SEKOLAH DASAR ISLAM TERPADU BAITUL HAMDI KOTA PADANG - Yuliani Fitri; Ambiyar; Ishak Aziz (Ekasakti Jurnal Penelitian dan Pengabdian, 2023)
Education evaluation through the Computer-Based National Assessment (ANBK) is used to assess the quality of each educational institution, including elementary schools, junior high schools and high schools. In 2021, ANBK was first put into use. Assessment focuses on students' literacy or reading and numeracy or counting skills. The purpose of this article is to examine how ANBK is implemented at the Baitul Hamdi Padang Integrated Islamic Elementary School (SD IT). This research is descriptive qualitative in nature. Research findings show that the implementation of ANBK will be carried out independently and online at SD IT Baitul Hamdi in 2023. The pre-ANBK stage, ANBK implementation stage, and post-ANBK stage are the three stages of ANBK implementation. Activities, outreach, personnel management, participant management, facilities and infrastructure management, are all part of the pre-ANBK stage. The school principal is trying to resolve problems arising from the lack of laptop availability so that the implementation of ANBK can run well. At SD IT Baitul Hamdi, the implementation of ANBK is generally in accordance with established protocols. Proctors and technicians have also completed their duties properly in accordance with the specified technical guidelines.